Comparative Analysis Of Cytochrome P450 Monooxygenases Between The Genera Streptomyces And Mycobacterium - Moshoeshoe, Senate (Central University of Technology, Free State, 2019)
Cytochrome P450 monooxygenases (CYPs/P450s) are found in all domains of life and are known for their catalytic versatility and stereo- and regio-specific activity. While the impact of lifestyle on P450 evolution has been reported in many eukaryotes, this remains to be addressed in bacteria. In this report, Streptomyces and Mycobacterium, belonging to the phylum Actinobacteria, were studied owing to their contrasting lifestyles and impact on human beings. Genome-wide data mining and annotation of P450s in 48 Streptomyces species revealed the presence of 1 625 P450s in their genomes. Of these 1 625 P450s, all had characteristic glutamic acid and cysteine at the EXXR and CXG motifs, respectively; however, 34 P450s lacked one or both P450 characteristic motifs, EXXR and CXG, owing to their short amino acid sequences and were thus regarded as fragment/pseudo-P450s. Comparison of P450s revealed that species belonging to the genera Streptomyces and Mycobacterium had almost the same patterns in terms of the average number of P450s in their genomes. All 1 625 P450 identified in 48 Streptomyces species were grouped into 144 P450 families and 377 P450 subfamilies. Among the families and subfamilies, 66 new P450 families and 144 new P450 subfamilies were identified in Streptomyces species. Analysis of P450 family conservation across 48 Streptomyces species revealed that among 144 P450 families identified, only two P450 families, the CYP107 and CYP157 P450 families, are conserved across all Streptomyces species. Comparative analysis of P450 family dynamics between the genera Streptomyces and Mycobacterium revealed the presence of the highest number of P450 families and P450 subfamilies in Streptomyces species. Streptomyces species have 144 P450 families and 377 P450 subfamilies, compared to 77 P450 families and 132 P450 subfamilies in mycobacterial species. Streptomyces species also have the highest number of new P450 families (66 families) and new P450 subfamilies (144 subfamilies) in their genomes compared to mycobacterial species. Interestingly, only two P450 families (CYP107 and CYP157) were conserved in Streptomyces compared to mycobacterial species where 10 P450 families, namely CYP51, CYP123, CYP125, CYP130, CYP135, CYP136, CYP138, CYP140, CYP144 and CYP1128, were conserved. Furthermore, P450 diversity percentage analysis between two genera revealed that Streptomyces species had almost double the P450 diversity percentage (0.18%) than mycobacterial species (0.07%). Comparative analysis of P450 profiles between the genera Streptomyces and Mycobacterium revealed that species belonging to these genera have different P450 profiles with few similarities. Despite both genera belonging to the same phylum, Actinobacteria, only 21 P450 families were found to be common and quite a large number of P450 families were found to be unique to Streptomyces (123 P450 families) and Mycobacterium (56 P450 families). In the 21 P450 families commonly found between the two genera, an interesting feature was observed in terms of the number of member P450s. A significant difference in the number of member P450s in the commonly shared P450 families was observed between Streptomyces and Mycobacterium. Differences were also observed in the number of dominant P450 families in the two genera. Only seven P450 families, namely CYP107, CYP105, CYP157, CYP154, CYP156, CYP147 and CYP183, contributed 62% of all P450s in Streptomyces species, whereas 15 P450 families, namely CYP125, CYP189, CYP150, CYP136, CYP135, CYP138, CYP140, CYP123, CYP143, CYP142, CYP144, CYP124, CYP108, CYP51 and CYP187, contributed 60% of all P450s in Mycobacterium. Furthermore, differences in P450 profiles between the two genera were observed in terms of type of dominant P450 families. A comparison of the dominant P450 families between the two genera revealed that none of the dominant P450 families was common between them. This strongly supports the concept that these Streptomyces P450s play a key role in the production of chemically diverse secondary metabolites, as a large number of P450 families were found in 48 Streptomyces species. P450 families, namely CYP105, CYP107, CYP161, and CYP183, which are highly populated in Streptomyces species compared to mycobacterial species, were found to be involved in secondary metabolite production. In contrast to the P450 families highly populated in Streptomyces species, P450 families that are highly populated in mycobacterial species, such as CYP125, CYP124, CYP108, CYP140 and CYP268, are involved in steroid (cholesterol) and hydrocarbon (lipids, alkenes, long chain acetate and ketone) hydroxylation, suggesting that these P450 families possibly help mycobacterial species to assimilate the host compounds. It is clear that different lifestyles influenced the P450 profiles in Streptomyces and Mycobacterium, hence the differences observed between the two genera in terms of number of P450s, P450 family and subfamily diversity, dominant and unique P450 families types and differences in number of P450s in common P450 families. Furthermore, functional analysis of P450s suggests that in Streptomyces, P450s are destined for secondary metabolite production, whereas in Mycobacterium they are destined for utilisation of host lipids or synthesis of novel lipids. Based on the evidence presented in this study, the researcher hereby proposes that lifestyle or ecological niches play a key role in the evolution of P450 profiles in species belonging to the genera Streptomyces and Mycobacterium.
Thesis